Genotype-Phenotype Associations of the CD-Associated Single Nucleotide Polymorphism within the Gene Locus Encoding Protein Tyrosine Phosphatase Non-Receptor Type 22 in Patients of the Swiss IBD Cohort - Spalinger, Marianne R. (PLoS One, 2016)
BACKGROUND: Protein tyrosine phosphatase non-receptor type 22 (PTPN22) plays an important role in immune cell function and intestinal homeostasis. The single nucleotide polymorphism (SNP) rs2476601 within the PTPN22 gene locus results in aberrant function of PTPN22 protein and protects from Crohn’s disease (CD). Here, we investigated associations of PTPN22 SNP rs2476601 in inflammatory bowel disease (IBD) patients in the Swiss IBD Cohort Study (SIBDCS). METHODS: 2’028 SIBDCS patients (1173 CD and 855 ulcerative colitis (UC) patients) were included. The clinical characteristics were analysed for an association with the presence of the PTPN22 SNP rs2476601 genotypes ‘homozygous variant’ (AA), ‘heterozygous’ (GA) and ‘homozygous wild-type’ (GG). RESULTS: 13 patients (0.6%) were homozygous variant (AA) for the PTPN22 polymorphism, 269 (13.3%) heterozygous variant (GA) and 1’746 (86.1%) homozygous wild-type (GG). In CD, AA and GA genotypes were associated with less use of steroids and antibiotics, and reduced prevalence of vitamin D and calcium deficiency. In UC the AA and GA genotype was associated with increased use of azathioprine and anti-TNF antibodies, but significantly less patients with the PTPN22 variant featured malabsorption syndrome (p = 0.026). CONCLUSION: Our study for the first time addressed how presence of SNP rs2476601 within the PTPN22 gene affects clinical characteristics in IBD-patients. Several factors that correlate with more severe disease were found to be less common in CD patients carrying the A-allele, pointing towards a protective role for this variant in affected CD patients. In UC patients however, we found the opposite trend, suggesting a disease-promoting effect of the A-allele.